Les processus d’autorégulation collective et individuelle au cours d’un apprentissage par projet - Laurent Cosnefroy; Annie Jézégou (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In order to get an insight into the processes underlying an efficient collective and individual self-regulation, a study was conducted with 73 students of a French-Engineering school engaged in a one-year project-based learning. Students were asked to fill up a questionnaire twice in December and in February. The results showed that perceived collective efficacy is a significant predictor of the final grade. They also enhanced the key role of setting precise goals, prioritizing them and adjusting them to support the development of collective efficacy and to help groups overcome difficulty. However, disagreements and asymmetrical interactions within group don’t have any influence on perceived collective efficacy. Knowledge acquisition is a major path to develop an individual interest for the project. Finally, implications for teaching in project-based learning are discussed.